EP1336 Complete tumor resection from porta hepatis in a patient with recurrent epithelial ovarian cancer. (1st November 2019) - Vatansever, D; Misirlioglu, S; Giray, B; Erkan, M; Balik, E; Arvas, M; Taskiran, C
Abstract : Introduction/Background: Ovarian cancer is the leading cause of death among gynecological malignancies. Even if a complete cytoreduction is achieved at the time of first surgery, about 60–70% of advanced stage patients develop a recurrence. Secondary cytoreductive surgery is associated with improved overall survival in patients with recurrent ovarian cancer. The aim of this video is to present complete tumor resection from porta hepatis in a patient with recurrent epithelial ovarian cancer. Methodology: A 50 years-old woman referred to our clinic with a diagnosis of recurrent epithelial ovarian cancer. She has undergone a primary maximal debulking surgery two years ago. The magnetic resonance imaging revealed multiple metastasis in liver. Total colectomy, ileostomy, liver metastasectomy, cholecystectomy, splenectomy, peritonectomy, lymphadenectomy, unilateral diaphragmatic stripping, and bilateral ureteroneocystostomy were performed as a part of maximal secondary cytoreduction. Results: She stayed at the intensive care unit for two day and discharged on post-operative day 6 without any grade 3 or 4 adverse event in post-operative period. Conclusion: Secondary cytoreductive surgery is associated with improved results in patients with recurrent ovarian cancer, and maximal cytoreduction is necessary in selected cases. Disclosure: Nothing to disclose